Investigation on the planar resonator for fabric based chipless RFID - Hossain, A. K. M. Zakir; -, Sanaullah; Azam, S. M. Kayser; Ibrahimy, Muhammad Ibn (IEEE, 2023)
This paper involves the investigation on the planar resonator with an intension for implementation in the fabric based chipless RFID (CRFID). The investigation is performed on two PCBs (Rogers 3003 and Rogers 5880) and five different fabric based substrates (pile, denim, silk, felt and fleece). S-parameter responses of the ‘Truncated C’ multiresonator (TCMR) on different substrate are characterized to find out the coding bit, effective bandwidth (EBW), fractional bandwidth (FBW−10dB), quality factor (Q-10dB), spectral density (bits/GHz). Finally, the resonator has been tested in different bending conditions. A 9-bit all presence coding of 111111111 has been extracted for all substrates by using S 21 vs Frequency plot. It is found that even though using fabric as substrate, the resonance dip goes as low as -35dB. The quality factor is found as high as 233.96 and the EBW is nominally constant between 1.55 GHz–1.65 GHz for all fabric based substrates. All results have indicated that the TCMR can be a good candidate for fabric based CRFID system.